Business Development Strategy for Kopi Kita MSME in Purbolinggo East Lampung Based on SWOT Analysis - Ika Larasati; Ervina Mela (Indonesian Journal of Food Technology, 2022)
Kopi Kita is one of the MSME that processes coffee beans into ground coffee. The challenge faced by SMEs is the intense business competition. Therefore it is necessary to formulate the right strategy to overcome this challenge based on the strengths, weaknesses, opportunities and threats that the company has. The purpose of this research is to examine and find out internal and external factors in the company and formulate and obtain relevant business development strategies to be applied to Kopi Kita, Purbolinggo, Lampung. The research method was carried out by observation, interviews, and literature study, while the data were analyzed using the SWOT method. The results of the study show alternative strategies for developing Coffee SME businesses are 1) maintaining and improving product quality, 2) maintaining product price stability, 3) increasing product marketing through digital media, 4) collaborating with the government in providing production facilities and infrastructure, 5) fixing the packaging, 6) maintaining product price stability and highlighting the characteristics and variety of products owned, 7) highlighting the composition contained in the product, 8) implementing rewards and punishment for employees.